An investigation into strategies of translating elements of humour in the vietnamese translation of walt disney animated films (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study has been carried out in an attempt to examine the most common strategies adopted in translating element of humour from English cartoons into Vietnamese equivalents. The data of the study were collected from 9 animated films of Walt Disney Animation Studios and their corresponding translated versions. Thirty segments were then chosen to be analyzed in detail in terms of the jokes’ types of humour, translational problems and the translators’ purposes. Under qualitative and quantitative approaches, the data were described and analyzed in linguistic and cultural aspects. In addition to the most preffered strategies employed in humour translation process, humour loss in translation and its probable causes were also discussed. From the results accomplished, some conclusions were drawn. It could be suggested that WD cartoon translated versions follow a less target text oriented strategy. Paraphrasing, literal translation, transposition, and omission are the most frequently used strategies to transfer humour in cartoon translation. Some contributing factors in rendering elements of humour which are Vietnamese idiomatic expressions and Vietnamese buffer words are figured out. Finally, some constructive suggestions were put forward to reduce loss phenomenon in humour transfer in cartoon translation and promote better translation as a work.